Translating lab success to the field: Evaluating coffee biochar-enhanced concrete in real-world construction - Rajeev Roychand; Shannon Kilmartin-Lynch; Mohammad Saberian; Jie Li; Chun Qing Li (Case Studies in Construction Materials)
Building upon our pioneering laboratory research on coffee biochar in concrete, this study presents a world-first field trial, translating lab-based findings into real-world construction applications. Our previous experimental work demonstrated that biochar derived from pyrolysing spent coffee grounds (SCGs) at 350°C, when used as a partial replacement of fine aggregates, could enhance concrete strength by up to ∼30 %. This field study evaluates the performance of coffee biochar-enhanced concrete under actual construction and environmental conditions. However, a major limitation was encountered in the production of coffee biochar, as the pyrolysis equipment of the commercial-scale biochar producer could not operate at the optimal 350°C temperature due to operational constraints. In this real-world application, we collaborated with a local council to translate the lab-based research work into a mainstream construction solution. To evaluate the performance of this biochar blended concrete, we carried out independent testing of the concrete slump, compressive strength of concrete and cored slab, flexural strength and concrete shrinkage and compared its performance against the control mix. The successful translation of this lab-based research into field applications showcases the potential of coffee biochar as a sustainable construction material that can transform coffee waste into a valuable resource for concrete applications with improved performance. It also highlights the current supply chain limitations that must be addressed before making it a mainstream construction material.